Psychological Aspects Of Pandu Roga (Anaemia) In Its Etiopathogenesis -A Review - Ahe, Ganesh T; Dobade, Deepak K (International Research Journal of Ayurveda & Yoga, 2021)
The Prime aim of Ayurveda is to maintain the positive health and to eradicate the illness in a diseased through holistic approach. Many patients are seen suffering from Pandu Roga (Iron deficiency anaemia) due to modern Stressful lifestyle, improper dietary habits and routine. There is loss of prabha (complexion) and kanti (glow) which is due to ras(plasma), rakta (blood) and ojakshaya (depletion of oja). Charakacharya has described some psychological etiological factors among which Chinta (worry), Shoka (grief) and Bhaya (fear) are three main factors, which play an important role in the etiopathogenesis of Pandu Roga (Iron deficiency anaemia). Anaemia is a disorder that develops when our blood lacks enough healthy red blood cells or haemoglobin. Haemoglobin is a main part of red blood cells and binds oxygen which refers to a decreased number of circulating red blood cells. Anaemia is a public health problem, although the primary cause is iron deficiency. More frequently it coexists with a number of other causes, such as nutritional deficiencies, malaria, parasitic infection, and haemoglobinopathies. In todays modernized lifestyle, we see many people in the community are suffering from psychological problems including stress, anxiety, depression etc. All these factors lead to mental illness and then Physical illness. According to the national mental health survey nearly 11% of Indians above 18 years are suffering from such disorders. The present paper aims to explore the scientific explanations for the above mentioned Psychological etiological factors in the causation of Pandu vyadhi (Anaemia).